PRESENCIA DE RHABDINOPORA (GRAPTOLITHINA) EN LA QUEBRADA DE HUMAHUACA, PROVINCIA DE JUJUY (Ameghiniana, 2014)
Large specimens of Early Ordovician planktic graptolites assigned to Rhabdinopora flabelliformis flabelliformis (Bulman) and Rhabdinopora flabelliformis socialis (Salter) were found near Hornaditas, Jujuy Province, northwestern Argentina, in gray greenish shales and fine-grained sandstones of the Santa Rosita Formation. This first finding within the middle part of the Cordillera Oriental is irnportant because Rhabdinopora has been regarded as a guide fossil for the Cambrian-Ordovician boundary worldwide.